IgG4-Related Kidney Disease: Report of a Case Presenting as a Renal Mass - Daniele Bianchi; Luca Topazio; Gabriele Gaziev; Valerio Iacovelli; Pierluigi Bove; Alessandro Mauriello; Enrico Finazzi Agrò (Case Reports in Surgery)
IgG4-related disease (IgG4-RD) is a nosological entity defined as a chronic immune-mediated fibro-inflammatory condition characterized by a tendency to form tumefactive, tissue-destructive lesions or by organ failure. Urologic involvement in IgG4-RD has been described in some short series of patients and in isolated case reports, most often involving the kidneys in so-called IgG4-related kidney disease (IgG4-RKD). The disease can occasionally mimic malignancies and is at risk of being misdiagnosed due to its rarity. We report the case of a 56-year-old man presenting with a right renal mass suspected of being malignant. Laboratory tests showed normal creatinine levels, a high erythrocyte sedimentation rate, and high levels of C-reactive protein and microalbuminuria. The patient underwent radical right nephroureterectomy and histopathologic examination revealed features proving IgG4-RKD. He was therefore referred to immunologists. Typical clinical presentation of IgG4-RKD includes altered renal function with inconstant or no radiologic findings. Conversely, in the case we presented, a single nodule was detected upon imaging evaluation, thus mimicking malignancy. This raises the issue of a proper differential diagnosis. A multidisciplinary approach can be useful, although in clinical practice the selection of patients suspected of having IgG4-RKD is critical in the cases presenting with a renal mass that mimics malignancy.